2021
DOI: 10.3390/jcm10214818
|View full text |Cite
|
Sign up to set email alerts
|

Prediction Accuracy of Serial Lung Ultrasound in COVID-19 Hospitalized Patients (Pred-Echovid Study)

Abstract: The value of serial lung ultrasound (LUS) in patients with COVID-19 is not well defined. In this multicenter prospective observational study, we aimed to assess the prognostic accuracy of serial LUS in patients admitted to hospital due to COVID-19. The serial LUS protocol included two examinations (0–48 h and 72–96 h after admission) using a 10-zones sequence, and a 0 to 5 severity score. Primary combined endpoint was death or the need for invasive mechanical ventilation. Calibration (Hosmer–Lemeshow test and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 29 publications
0
21
0
Order By: Relevance
“…Recently, LUS has proved its efficiency in the dynamic monitoring of COVID-19 pneumonia, as well as in the follow-up of patients recovered from this infection [ 63 , 64 ]. Moreover, a recent review proves the usefulness of hand-held ultrasound equipment, which has the advantage of lower acquisition costs and that is easy to decontaminate, which is a necessary activity nowadays [ 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, LUS has proved its efficiency in the dynamic monitoring of COVID-19 pneumonia, as well as in the follow-up of patients recovered from this infection [ 63 , 64 ]. Moreover, a recent review proves the usefulness of hand-held ultrasound equipment, which has the advantage of lower acquisition costs and that is easy to decontaminate, which is a necessary activity nowadays [ 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the last decades, LUS has proven to be a suitable alternative to conventional radiological methods in multiple kinds of lung diseases (24)(25)(26)(27). During the current pandemic, numerous studies have reported the usefulness of LUS as a front-line tool in the diagnosis and management of SARS-CoV-2 acute pneumonia (28)(29)(30)(31). However, its applicability in the detection of post-COVID-19 interstitial sequelae is yet to be defined.…”
Section: Introductionmentioning
confidence: 99%
“…While these results suggest clinicians felt the potential advantages of LUS did not consistently outweigh barriers to use in the management of all patients with COVID-19, it is important to note that the perceived barriers are likely dynamic. For instance, lack of evidence for support of LUS in COVID-19 could change with time as there have been multiple studies demonstrating utility in COVID-19 published since our pilot ended [34][35][36]. This may allow a more targeted approach to utilize LUS in the COVID-19 patients who would most benefit.…”
Section: Discussionmentioning
confidence: 99%